NEW SOUTH ASIAN-AMERICAN FICTION: MERGENCE OF A NEW GENRE? - Munir Khan (Celt: A Journal of Culture, English Language Teaching & Literature, 2011)
This paper, uNew South Asian-American Fiction: Emergence of a New Genre?" focuses on a group of emerging South Asian-American novelists in the last decade, who give a new consciousness to fiction. With their multicultural, multireligious, multilingual and multiethnic traditions, the newly discovered writers settled in America are growing fast with new identity. Gifted with tremendous creative eneTgY, they seize and give artistic shape to experiences in America. Enjoying a certain degree of critical contributions, their writings, as a distinct area of literary study, are unlike the other migrant ones which mostly have reflected the angst and trauma of the 'Nowhere man '. Their fictional writings have acquired a shape of spiritual quest that yields eventually towards a sense of equilibrium, establishing the in-between space as one of creativity, enrichment, and survival. The paper tries to show how the current crop of the South Asian writers in America creates a literary tradition that is formally and thematically different with a special reference to Manil Suri's The Death of VIShnu. With a spirit of religious revivalism, they try to re-make themselves in writing a new genre and new form beingforged. Their individual styles, new idioms, and diversity of thematic patterns also point to the changing complexions of lndianAmerican Literature.